METAPHORICAL FOUNDATIONS OF PHRASEOLOGISMS OF PATIENCE AND ENDURANCE - Raxmanova Sarvinoz Alisherovna (American Journals, 2025)
This article analyzes the metaphorical foundations of the phraseological units «sabr» and «chidam» in the Uzbek language. The study reveals the concepts of patience, endurance and willpower formed in the popular thinking through phraseologisms. Based on the method of metaphorical analysis, the semantic, cognitive and axiological (value) properties of the expressions «sabr» and «chidam» were studied. The results of the analysis show that these phraseologisms are based on metaphorical models such as nature, time, power and stone in the popular thinking. These units are manifested as a cultural-linguistic system expressing a person's mental state, attitude to life's trials and willpower. The results of the article serve to further enrich the cognitive interpretation of metaphors and phraseologisms in the Uzbek language.
Keywords: Patience, endurance, phraseology, metaphor, cognitive analysis, axiology, semantic model, volition, cultural concept.